2016
DOI: 10.5194/acp-16-4661-2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-range aerosol transport on the microphysical properties of low-level liquid clouds in the Arctic

Abstract: Abstract. The properties of low-level liquid clouds in the Arctic can be altered by long-range pollution transport to the region. Satellite, tracer transport model, and meteorological data sets are used here to determine a net aerosol-cloud interaction (ACI net ) parameter that expresses the ratio of relative changes in cloud microphysical properties to relative variations in pollution concentrations while accounting for dry or wet scavenging of aerosols en route to the Arctic. For a period between 2008 and 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 96 publications
(141 reference statements)
1
35
0
Order By: Relevance
“…Riedi et al (2010) showed that the distribution of Φ can be divided in eight regimes around 20 for high confidence liquid, around 50 for confident liquid, around 80 for liquid, around 100 for mixed phase, around 120 for low confidence ice, 150 for confident ice, and 180 for high confidence ice. Coopman et al (2016) showed that, for Arctic clouds, Φ can be divided into three regimes ranging from 0 to 60 for liquid clouds, from 60 to 140 for clouds of unknown phase (i.e., broken clouds with unreliable phase retrievals), and from 140 to 200 for ice clouds.…”
Section: Datamentioning
confidence: 99%
“…Riedi et al (2010) showed that the distribution of Φ can be divided in eight regimes around 20 for high confidence liquid, around 50 for confident liquid, around 80 for liquid, around 100 for mixed phase, around 120 for low confidence ice, 150 for confident ice, and 180 for high confidence ice. Coopman et al (2016) showed that, for Arctic clouds, Φ can be divided into three regimes ranging from 0 to 60 for liquid clouds, from 60 to 140 for clouds of unknown phase (i.e., broken clouds with unreliable phase retrievals), and from 140 to 200 for ice clouds.…”
Section: Datamentioning
confidence: 99%
“…Previous estimates of the ACI index values in the Arctic ranged between 0.0 and 0.19 when remote sensing data or limited aircraft in situ data were used (Coopman et al, 2016;Garrett et al, 2004;Tietze et al, 2011;Zamora et al, 2016), although values close to 0.33 were derived in limited cases (Coopman et al, 2018). Compared with these estimates, the values of 0.22-0.24 obtained in this study are systematically higher and are generally in agreement with those of 0.2-0.3 obtained using ground-based in situ measurements in the Pallas area of northern Finland (68°N, 24°E; Lihavainen et al, 2010).…”
Section: 1029/2018jd029802mentioning
confidence: 99%
“…In these studies, tracer transport models or global chemistry models have also been used to estimate aerosol amounts. As a result, ACI index values between 0.0 and 0.19 were derived (Coopman et al, 2016;Garrett et al, 2004;Tietze et al, 2011), although values close to 0.33 were derived in limited cases (Coopman et al, 2018). By combining the in situ measurements made during several aircraft experiments in the Arctic, ACI index values of approximately 0.16 were also derived (Zamora et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature inversions, both surface and elevated, are very commonly observed meteorological phenomena in the Arctic especially during winter and early spring (Tjernström & Graversen, 2009). They influence the dispersion of aerosols, their contribution to the vertical distribution of radiative heating, and the way aerosols affect Arctic cloud and radiation processes (Coopman et al, 2016). Characterizing covariability of temperature inversions and aerosol distribution would shed light not only on the transport pathways into the Arctic, depending on if aerosol accumulation occurs above the inversion layer or below, but also help in better understanding aerosol radiative effects.…”
Section: 1029/2018gl081624mentioning
confidence: 99%